The links between technology and principles of language teaching and learning: theoretical and practical insights - Alsolami, Turki; Saaty, Nashwa (Technium Social Sciences Journal, 2020)
The paper examines the integration of technology into various language learning aspects, mainly how technology can enhance language learning and teaching. The focus is on selected studies that highlight the significant role of technology in promoting higher levels of motivation, enhancing language input, contextualizing the language learning process through access to various cultural materials, improving learners’ L2 attitudes and enhancing better language teaching instruction. In examining these areas, we hope to provide pedagogical insights that would help practitioners and curriculum developers to utilize technology in an effective way to promote a better language learning experience.